Improving Performance: The Role Of Teacher Professionalism And Discipline At The Tahsinul Akhlaq Bahrul Ulum Foundation Surabaya - M. Mushthofa Mubasysyir; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
Quality education depends not only on the physical infrastructure of the school, but also on the competence and dedication of the teachers. Professionalism and discipline are the main elements that can improve the quality of education and teacher performance. This research is to analyse the influence of professionalism and discipline on teacher performance at the Tahsinul Akhlaq Bahrul Ulum Foundation, Surabaya. Teacher performance is a central factor in educational dynamics. Teacher professionalism directly influences the quality of teaching. Teachers' discipline determines their ability to carry out their duties and responsibilities efficiently. This research uses a quantitative approach with a survey research design. The population involved all teachers at the Tahsinul Akhlaq Bahrul Ulum Surabaya Foundation, with census sampling of 65 teachers. The instrument used is a questionnaire that measures the level of professionalism, discipline and teacher performance. The research results show that the level of professionalism of teachers at the Tahsinul Akhlaq Bahrul Ulum Surabaya Foundation has a positive and significant influence on their performance. Teachers who have competence, dedication and professional skills tend to make a positive contribution to achieving educational goals. Apart from that, teacher discipline also has a positive and significant impact on their performance. Teachers who are disciplined in carrying out their duties, obey the rules, and show commitment to their work, tend to achieve better results in educating and guiding students